The Relationship between Learning Styles and Creative Thinking and Problem-Solving Abilities of Students at SMK Negeri 1 Kisaran - Muhammad Razali; Cut Latifah Zahari (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
The aim of this study is to examine the impact of students’ learning styles visual, auditory, and kinesthetic on their creative thinking and problem-solving abilities. This research employed a quantitative approach with a comparative descriptive method. Data were collected through descriptive and inferential analysis. The study population consisted of 340 eleventh-grade students of SMK Negeri 1 Kisaran, from which 78 students were selected as samples using purposive sampling. Research instruments included a 39-item learning style questionnaire, 5 items measuring mathematical creative thinking skills, and 5 items assessing problem-solving skills. Data were analyzed using multivariate techniques with the MANOVA test. The findings indicate that learning styles significantly influence both creative thinking and problem-solving abilities, with a contribution of 57.1%. This result suggests that students’ visual, auditory, and kinesthetic learning styles play an important role in shaping their creative thinking and problem-solving skills.